World health organization: forum 8 + world summit on health research Mexico city, november 6-10, 2004 - Cruz, Isabel Cristina Fonseca da (Online Brazilian Journal of Nursing, 2004)
Call for abstracts: Deadline for receipt of proposals is 31 May, 2004. Key topics include: - The 10/90 gap in health research and the MDGs - Contributions towards reaching the MDGs from the public sector, the private sector and civil society - Cross-cutting issues and the MDGs, such as poverty, equity, gender, disability, research capacity strengthening, youth and ageing - Research to deliver better health to families and communities, including health research for improved child and maternal health and for a sustainable environment - Health research on diseases and determinants, including communicable, noncommunicable and chronic diseases, injuries and violence - Measuring progress towards the MDGs, including financial flows, priority setting and indicators of progress - Partnerships in health research for development, including networks and public-private partnerships.